The Biodiversity and Geochemistry of Cryoconite Holes in Queen Maud Land, East Antarctica - Lutz, Stefanie; Ziolkowski, Lori A.; Benning, Liane G. (2019)
Cryoconite holes are oases of microbial diversity on ice surfaces. In contrast to the Arctic, where during the summer most cryoconite holes are ‘open’, in Continental Antarctica they are most often ‘lidded’ or completely frozen year-round. Thus, they represent ideal systems for the study of microbial community assemblies as well as carbon accumulation, since individual cryoconite holes can be isolated from external inputs for years. Here, we use high-throughput sequencing of the 16S and 18S rRNA genes to describe the bacterial and eukaryotic community compositions in cryoconite holes and surrounding lake, snow, soil and rock samples in Queen Maud Land. We cross correlate our findings with a broad range of geochemical data including for the first time 13C and 14C analyses of Antarctic cryoconites. We show that the geographic location has a larger effect on the distribution of the bacterial community compared to the eukaryotic community. Cryoconite holes are distinct from the local soils in both 13C and 14C and their isotopic composition is different from similar samples from the Arctic. Carbon contents were generally low (≤0.2%) and older (6–10 ky) than the surrounding soils, suggesting that the cryoconite holes are much more isolated from the atmosphere than the soils.